Cellular immunity in Holstein cows seropositive for Bovine Leukosis Virus (BLV) during the transition period - Gomes, V.; Baldacim, V. A. P.; Costa, J. F. R.; Costa e Silva, C. P.; Arcaro, J. R. P.; Miranda, M. S.; Sousa, R. S.; Fagliari, J. J. [UNESP]; Madureira, K. M. (Arquivo Brasileiro Medicina Veterinaria Zootecnia, 2017)
This research evaluated the dynamics of leukocytes and lymphocytes subsets in seropositive Holstein cows for BLV during the transition period. Blood samples (n= 72) from 12 cows were harvested from week -2 up to week + 3 to perform leukogram, immunophenotyping, cortisol and haptoglobin (Hp). Leukocytes pattern was characterized by leukocytosis, neutrophilia, monocytosis and eosinopenia around calving. Lymphocytosis and high proportions of B cells CD21+ were a constant finding between week -2 and + 3, thus cows were tested and confirmed seropositive for BLV. The values of T lymphocytes subsets were low during the transition period, observing two peaks that coincided with high levels of cortisol at delivery (2.11 mu g/dL) and week + 3 (1.97 mu g/dL). Hp had gradual increase from week -2 (166 mu g/mL) until week + 3 (576g/mL) probably due to high rate of uterine infection detected between week + 2 and + 3. The seropositive cows for BLV presented stress leukogram around delivery, except for lymphocytes. Lymphocytosis and the high proportions of B cells, associated with the low proportions of T lymphocytes, can be indicative of immunosuppression and predisposition to the inflammatory process observed in the post-partum period.
Keywords: peripartum; haptoglobin; cortisol; lymphocytes subsets